The correlatiion between parents’ educational attitudes and ethnocentrism among adolescents - Pavićević, Miljana S.; Petrović, Danijela S. (Collection of Papers of the Faculty of Philosophy in Priština, 2016)
The paper discusses the contribution that family upbringing has on the development of ethnocentrism among adolescents. This study included 345 respondents from Kosovo and Metohija of Serbian nationality. The following instruments were used for data collection: a scale for assessing educational attitudes of parents (Kodžopeljić, 2009) and the Scale for the assessment of ethnocentrism (SRAM, 2010). The research results show that adolescents exhibiting the highest level of national homogenization, and that according to their procenidominantan educational attitude of their parents cold-limiting. Correlation analysis is utvrđenanajveća association (r = is 0. 35) between the confining upbringing father and national superiority or bias and ethnic exclusion and prejudice. On the other hand, the highest correlation (r = is 0. 37) was found between mothers and cold upbringing national homogenization, as well as between confining education of mothers and ethnic exclusion and prejudice. Also, the correlation of medium intensity (r = is 0. 30 = r is 0. 49) exist between a cold upbringing mothers and ethnic exclusion and prejudice (r = is 0. 30); mothers and permissive upbringing national homogenization (r = is 0. 35); confining education of mothers and national superiority or bias (r = is 0. 35). In addition, regression analysis showed that parental attitudes mother significant predictors of all four aspects of ethnocentrism, while the educational attitude father a significant predictor only one aspect of ethnocentrism and national superiority or bias.